Percutaneous ballon compression for recurrent TN —a retrospective study of 33 cases - Feng, Dongwei; Zhang, Yaxin; Li, Dong; Wang, Kang; Yang, Fan; Ding, Jianan; Wu, Weize; Wang, Yunhe; Jia, Heping (Frontiers in Neurology, 2023)
Objective To investigate the clinical efficacy of percutaneous microballoon compression in the treatment of recurrent TN. Methods This retrospective study included 33 patients who underwent percutaneous microballoon compression for the treatment of recurrent TN from March 2019 to May 2022. Postoperative pain recurrence and facial numbness were assessed according to the Barrow Neurological Institute (BNI) pain score. Patients’ anxiety and sleep status during follow-up were assessed according to the Self-rating Anxiety Scale (SAS) and Pittsburgh Sleep Quality Index (PSQI). Results All patients (33 cases) were followed up for 12–38 months, with an average follow-up time of 23 months. On postoperative day 1, 31 patients (93.9%) reported no pain, and 2 patients were given drug treatment for pain relief, The total efficacy was 93.9%. Moreover, 2 patients (6.1%) reported significant pain relief 2 weeks postoperatively. There are many complications during and after PBC. The incidence of the trigeminocardiac reflex (TCR) during surgery was 100%, and the incidence of facial numbness, masseter muscle weakness, labial herpes and headache was 97, 60.6, 12.1 and 3%. No patient experienced severe facial numbness, hearing impairment, diplopia, injury to cranial nerves, Meningitis, intracranial haemorrhage or keratitis. 1 patient had recurrence of pain at 6 months post-op, which was relieved by oral medication. 81.8% suffered from anxiety and 54.5% had poor sleep quality before surgery. After the period of PBC, SAS and PSQI scores decreased continuously. There were significant improvements in anxiety and sleep status postoperatively compared with preoperatively. Conclusion PBC is a safe and effective option for the treatment of recurrent TN. The arduous and demanding nature of the clinical course subjects the patient to severe pain, mental, and physical stress. Thankfully, it significantly improves the symptoms of anxiety, depression, and sleep quality.